Does Venture Capital Reputation Contribute to Pre-IPO Performance of Entrepreneurial Firms in the Chinese Context?. (November 2022) - Long, Hai; Zhao, Jianzhi; Lin, Xiaochen; Liu, Lanyong
This study investigates venture capital (VC) reputation impact on the pre-IPO performance of the entrepreneurial firms backed by three kinds of VCs. This study employs backward stepwise regression models following prior theoretical frameworks to examine the research question. Based on a database of the top 50 VC firms ranked during 2016 to 2020 and their portfolio firms. This study shows some contingent contribution to pre-IPO firm performance. Firstly, the reputation of the Chinese government-owned VCs is negatively associated with their portfolio firm performance. Still, there is a positive relationship between foreign and local private VCs. Secondly, entrepreneurial firm performance is significantly associated with industry policy and entrepreneur's performance than VC reputation. This study has practical implications for entrepreneurs and limited partners regarding their corporation relationships with the Chinese VCs. JEL codes: G24, G34